42.8k views
1 vote

a = \frac{ {(x + 2)}^(2) - {(2x - 3)}^(2) }{ - x + 5}
make a in the simplest form

User Duddel
by
5.1k points

1 Answer

7 votes

Answer:


a=3x-1

Explanation:

Given:


a=((x+2)^2-(2x-3)^2)/(-x+5)

Use formulas


(u+v)^2=u^2+2uv+v^2\\ \\(u-v)^2=u^2-2uv+v^2

Therefore,


(x+2)^2=x^2+2\cdot x\cdot 2+2^2=x^2+4x+4\\ \\(2x-3)^2=(2x)^2-2\cdot (2x)\cdot 3+3^2=4x^2-12x+9

Now


(x+2)^2-(2x-3)^2\\ \\=x^2+4x+4-(4x^2-12x+9)\\ \\=x^2+4x+4-4x^2+12x-9\\ \\=-3x^2+16x-5

Factor it:


-3x^2+16x-5\\ \\=-3x^2+15x+x-5\\ \\=-3x(x-5)+(x-5)\\ \\=(x-5)(-3x+1)

Hence, the fraction can be simplified as follows:


a=((x-5)(-3x+1))/(-x+5)\\ \\a=((x-5)(-3x+1))/(-(x-5))\\ \\a=(-3x+1)/(-1)\\ \\a=3x-1

User Joe Pallas
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.